2012
DOI: 10.1002/hep.25631
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus selectively perturbs the distal cholesterol synthesis pathway in a genotype-specific manner

Abstract: Hepatitis C virus (HCV) subverts host cholesterol metabolism for key processes in its lifecycle. How this interference results in the frequently observed, genotype-dependent clinical sequelae of hypocholesterolemia, hepatic steatosis, and insulin resistance (IR) remains incompletely understood. Hypocholesterolemia typically resolves after sustained viral response (SVR), implicating viral interference in host lipid metabolism. Using a targeted cholesterol metabolomic platform we evaluated paired HCV genotype 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 39 publications
(36 reference statements)
3
51
0
Order By: Relevance
“…[28,29] All our HCV-4 patients had suboptimal vitamin D levels with the majority being severely deficient (86%). Possible explanations for the association of HCV with vitamin D deficiency have included decreased 25-alpha hydroxylation in the liver, HCV may have the ability to directly suppress 25-alpha hydroxylation through inducing cytokines and oxidative stresses, and a recent study has shown that HCV alters lipid metabolism directly reducing production of 7-dehydrocholesterol, the precursor of endogenouslyproduced vitamin D. [30,31] The independent effect of HCV on vitamin D levels is strongly supported by our finding of the remarkable improvement in vitamin D levels after successful eradication of HCV and its persistence in non-responders. Further studies are definitely recommended to depict the exact mechanisms by which HCV alters vitamin D production and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[28,29] All our HCV-4 patients had suboptimal vitamin D levels with the majority being severely deficient (86%). Possible explanations for the association of HCV with vitamin D deficiency have included decreased 25-alpha hydroxylation in the liver, HCV may have the ability to directly suppress 25-alpha hydroxylation through inducing cytokines and oxidative stresses, and a recent study has shown that HCV alters lipid metabolism directly reducing production of 7-dehydrocholesterol, the precursor of endogenouslyproduced vitamin D. [30,31] The independent effect of HCV on vitamin D levels is strongly supported by our finding of the remarkable improvement in vitamin D levels after successful eradication of HCV and its persistence in non-responders. Further studies are definitely recommended to depict the exact mechanisms by which HCV alters vitamin D production and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Secondly, another problem that is not well understood is the interaction between HCV and lipid metabolism. [16] So, HCV G3 selectively interferes with the late cholesterol synthesis pathway, [17] although this interference is resolved after the SVR. Other mechanisms that alter lipid metabolism are increased the novo lipogenesis and the inhibition of mitochondrial fatty acid degradation.…”
Section: Editorialmentioning
confidence: 99%
“…Our study indicated that the distal post-squalene sterol metabolites lathosterol, desmosterol and 7-DHC were lower in GT3 patients compared to GT2. A prior small study in 33 CHC patients (GT2=13, GT3=20) treated with IFN-based therapy indicated no baseline genotype differences in distal sterol metabolites, except for 7-DHC [21].In contrast, our study included a larger cohort with both fibrosis assessment and sterol metabolite measurement at end-of-treatment, to allow for clinically relevant subgroup analyses in relation to genotype, relapse, and advanced disease. In addition, our study also demonstrated on-treatment increases in desmosterol and lanosterol for GT3 patients, and a novel independent association between baseline lathosterol and SVR.…”
Section: Discussionmentioning
confidence: 94%
“…A small pilot study demonstrated HCV GT3-specific perturbation of distal cholesterol biosynthesis metabolites but the preservation of proximal metabolites such as lanosterol [21]. However, the pathogenic mechanisms and reasons for this genotype-specific inhibition of cholesterol biosynthesis pathway to provide a survival advantage to the virus are poorly understood.…”
Section: Introductionmentioning
confidence: 99%